Analysis Using High-Precision Airborne LiDAR Data to Survey Potential Collapse Geological Hazards - Jinxing She; Awei Mabi; Zhongming Liu; Mingqiang Sheng; Xiujun Dong; Fei Liu; Shiyang Wang (Advances in Civil Engineering)
On August 8, 2017, an earthquake of magnitude 7.0 on the Richter scale occurred in Jiuzhaigou, Sichuan, causing significant damage to both life and property. Traditional geological hazard investigation is difficult in Jiuzhaigou because of the high altitude, the high-altitude canyons, and the vegetation-covered seismic areas. This study explores the technical advantages of using airborne LiDAR technology to penetrate vegetation and gather information directly from the surface, rapidly acquiring airborne 3D point cloud data in difficult areas. Through the preprocessing of data, the high-precision digital terrain and landform results were obtained. Comparative research found that the DEM obtained by high-precision airborne LiDAR technology has significant advantages in terms of the accuracy, details, and microgeomorphology of the data collected. The results can be directly used in the early identification of disasters, such as during the initial collapse or for disaster management. Studies have shown that airborne LiDAR has the technical advantage of penetrating vegetation to the surface and can, therefore, be used to guide the early identification and management of geological disasters in similar areas in the future.